A mediated model of E-WOM effects towards continuous use intention of social commerce - Noori, Atyaf Sami (2019)
Electronic Word of Mouth (e-WOM) plays a significant role in influencing users’ behavioural intention in social commerce (s-commerce). Research on the influence of perceived attributes of e-WOM on continuous use intention of s-commerce is limited to users’ attitudes in continuous usage of s-commerce. However, other contextual factors like trust and commitment are very crucial in sustaining a seller-buyer relationship on s-commerce. Moreover, there has been fierce competition to retain customers and ensure continuous usage of s-commerce to gain competitive advantage. This study integrates Technology Acceptance Model (TAM) and Commitment-Trust Theory (CTT) to examine the relationship between perceived attributes of e-WOM, trust, commitment, and continuous use intention of s-commerce. The framework also examines the mediational effects of those factors and their relationships. This study adapts post-positivism paradigm and quantitative research method. Data was collected from 365 s-commerce users in Malaysia through online survey. The data was analysed using statistical analysis techniques and Structural Equation Modelling. The results showed that continuous use intention is significantly affected by perceived usefulness, ease of use, and enjoyment of e-WOM. It is also revealed that trust and commitment significantly affected continuous use intention. Meanwhile, perceived ease of use and perceived enjoyment are found to significantly influence trust. Furthermore, perceived enjoyment influenced commitment only. Additionally, trust significantly mediated the relationship between perceived usefulness, perceived enjoyment and continuous use intention. Lastly, commitment significantly mediated the relationships between perceived ease of use, perceived enjoyment, and continuous use intention. Theoretically, this study contributes by incorporating CTT and TAM to show the relationship for perceived attributes of e-WOM, trust, and commitment in the context of continuous use of s-commerce. Practically, it provides knowledge about the factors that are vital to businesses operating over the s-commerce platforms.